Preparation method of shape-controllable iron-molybdenum formaldehyde catalyst

The iron-molybdenum catalyst is prepared by the complexation-sol-gel method, which solves the problems of low activity, poor selectivity and large amount of wastewater in the existing technology, realizes a catalyst with controllable morphology, is suitable for the needs of different industries, improves catalytic activity and selectivity, reduces wastewater generation, and realizes a green and environmentally friendly production process.

CN120618476AActive Publication Date: 2025-09-12BEIJING INSTITUTE OF PETROCHEMICAL TECHNOLOGY +1

Patent Information

Application Number
CN202510755698.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-07
Publication Date
2025-09-12
Estimated Expiration
2045-06-07

AI Technical Summary

Technical Problem

Existing iron-molybdenum formaldehyde catalysts have problems such as low activity, poor selectivity, single morphology and structure, large wastewater volume, and high wastewater treatment costs, making it difficult to meet the needs of different industries.

Method used

The iron-molybdenum catalyst was prepared by the complexation-sol-gel method. By adjusting the type and dosage of the complexing agent, controlling the pH and drying conditions, catalysts with different morphologies and particle sizes were prepared, including small-sized particles, large-sized particles, blocks and clusters, avoiding the formation of free flake MoO3.

Benefits of technology

The prepared catalyst has excellent comprehensive performance, is suitable for the needs of different industries, improves catalytic activity and selectivity, reduces wastewater generation, and realizes a green and environmentally friendly production process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120618476A_ABST
    Figure CN120618476A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a shape-controllable iron-molybdenum formaldehyde catalyst, and belongs to the technical field of catalyst preparation. The preparation method of the catalyst comprises the following steps: firstly, respectively mixing ammonium heptamolybdate tetrahydrate, ferric nitrate nonahydrate and a complexing agent, and dissolving in water to prepare a molybdenum-containing solution and an iron-containing solution; then mixing the molybdenum-containing solution and the iron-containing solution, adjusting the pH value, carrying out vacuum rotary evaporation to form sol, finally drying the sol to form xerogel, and roasting the xerogel to obtain a catalyst finished product. The coordination environment of Mo and Fe in the precursor solution is regulated and controlled through the complexing agent, uneven distribution of components is prevented, the uniform precursor solution is formed, the morphology and particle size of the catalyst are influenced by adjusting the pH of the solution and changing the precipitation rate of the precursor and the growth process of particles, and the catalyst with different morphologies and excellent comprehensive performance is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalyst preparation, and in particular to a method for preparing a morphology-controllable iron-molybdenum formaldehyde catalyst. Background Art

[0002] Formaldehyde is an important basic organic chemical raw material, widely used in the chemical, pharmaceutical, textile, wood processing, and petroleum industries. Modern industrial formaldehyde production primarily utilizes an oxidation process using methanol as the raw material. However, the "iron-molybdenum process" for formaldehyde production is widely used, and research on iron-molybdenum formaldehyde catalysts is ongoing.

[0003] For example, Chinese patent CN112657504A discloses a coating catalyst for methanol oxidation to formaldehyde by iron-molybdenum method and its preparation method. The catalyst is composed of an active component and an inert carrier. The active component structure is Mo. a Fe b Cu c X d O e The catalyst is prepared by coprecipitating ammonium heptamolybdate and ferric nitrate under the action of ultrasound and a dispersant to produce an Fe-Mo phase suspension system A; preparing an ammonium heptamolybdate aqueous solution, adjusting the solution pH, and adding a nitrate of metal X to produce system B; and, under the action of an ultrasound reaction environment and a complexing agent, allowing ammonium heptamolybdate and a copper salt aqueous solution to undergo a complexation reaction to produce a Cu-Mo sol system. A surfactant, system B, and system A are then sequentially added to the sol to carry out a synthesis reaction. The resulting slurry is spray-dried and calcined to produce an active component. A binder and a strength modifier are mixed into the active component, and the active component is coated on the surface of a spherical inert carrier by roll coating. The catalyst is then dried and calcined to produce the catalyst. However, the catalyst prepared by this method has a low formaldehyde yield.

[0004] In addition, the iron-molybdenum formaldehyde catalyst in the prior art has the following disadvantages:

[0005] 1. The active center of the iron-molybdenum formaldehyde catalyst is Fe2(MoO4)3 (Mo / Fe ratio is 1.5), while the Mo / Fe ratio of industrial iron-molybdenum catalysts ranges from 2.0 to 2.8. The presence of excess Mo can replenish Mo lost during the reaction and improve catalyst life. However, if excess Mo exists in the form of free flake MoO3, it will reduce catalyst activity and poor selectivity.

[0006] 2. The morphology, structure, and performance of industrially used formaldehyde catalysts are limited, making it difficult to meet the requirements of different industries. For example, the BDO industry does not require a high methanol content in formaldehyde products, but has strict requirements on formaldehyde selectivity. Therefore, catalysts with high formaldehyde selectivity should be selected to reduce methanol consumption (methanol consumed to produce one ton of formaldehyde solution) and lower production costs. In the aldehyde-aldehyde condensation or ester-aldehyde condensation process, methanol and water are required as solvents to avoid formaldehyde polymerization. Therefore, there is no requirement for methanol conversion rate. Catalysts with extremely high formaldehyde selectivity are suitable to achieve near-complete utilization of methanol molecules. The polyester industry has high requirements for methanol content in formaldehyde products, so catalysts with high activity (high methanol conversion rate) should be selected.

[0007] 3. The production process of iron-molybdenum formaldehyde catalyst mostly adopts the co-precipitation method, which has problems such as large amount of wastewater and high wastewater treatment cost, and has poor environmental protection and economic efficiency. Summary of the Invention

[0008] In view of this, the purpose of the present invention is to provide a method for preparing a morphology-controllable iron-molybdenum formaldehyde catalyst to improve the activity and selectivity of the iron-molybdenum formaldehyde catalyst.

[0009] In order to solve the above problems, the present invention adopts the following technical solutions:

[0010] A method for preparing a morphology-controllable iron-molybdenum formaldehyde catalyst comprises the following steps:

[0011] (1) adding ammonium heptamolybdate tetrahydrate to deionized water, then adding a complexing agent therein and fully dissolving it to obtain a molybdenum-containing solution;

[0012] (2) adding ferric nitrate nonahydrate to deionized water, and then adding a complexing agent thereto to fully dissolve the ferric nitrate to obtain an iron-containing solution;

[0013] (3) mixing the molybdenum-containing solution and the iron-containing solution to obtain a mixed solution, then adding ammonia to adjust the pH to 4.0-7.0, and stirring at room temperature;

[0014] (4) vacuum rotary evaporation of the solution in step (3) to form a sol;

[0015] (5) drying the sol from step (4) to form a xerogel;

[0016] (6) The xerogel obtained in step (5) is placed in a muffle furnace and calcined to obtain a finished catalyst product.

[0017] Preferably, the concentration of ammonium heptamolybdate in the molybdenum-containing solution in step (1) is 0.04-0.1 mol / L; and the molar ratio of the complexing agent to molybdate is 3:1-1:1.

[0018] Preferably, the concentration of ferric nitrate in the iron-containing solution in step (2) is 0.3-0.5 mol / L; and the molar ratio of the complexing agent to the iron ions is 3:1-1:1.

[0019] Preferably, the complexing agent in step (1) and step (2) is any one or more of citric acid, oxalic acid, ethylene glycol, ethylenediamine, ethylenediaminetetraacetic acid, glucose and 8-hydroxyquinoline.

[0020] Preferably, the molar atomic ratio of Mo to Fe in the mixed solution of step (3) is 2.1-2.3.

[0021] Preferably, the stirring time at room temperature in step (3) is 1-2 h.

[0022] Preferably, the temperature of the vacuum rotary evaporation in step (4) is 50-75°C.

[0023] Preferably, the drying temperature in step (5) is 90-100° C., and the drying time is 5-6 hours.

[0024] Preferably, the calcination temperature in step (6) is 500-550° C., and the calcination time is 10-12 hours.

[0025] In the present invention, the complexing agent can regulate the coordination environment of Fe and Mo in the precursor solution, preventing uneven distribution of components and forming a uniform precursor solution. Furthermore, by adjusting the pH of the solution, the precipitation rate of the precursor and the particle growth process can be changed, affecting the morphology and particle size of the catalyst.

[0026] For the surface-catalyzed methanol oxidation to formaldehyde reaction, the larger the specific surface area, the higher the reaction activity. Small-sized granular catalysts (particle size of 20-100nm) have a large specific surface area and the highest activity; block catalysts have a smaller specific surface area and a lower exposure of active centers, which avoids excessive oxidation of formaldehyde to CO and CO2, so the formaldehyde selectivity is higher; cluster catalysts have the smallest specific surface area. Although the methanol conversion rate is very low, the formaldehyde selectivity is extremely high, which can greatly reduce the unit consumption of methanol; large-sized granular catalysts (particle size of 100-300nm) have a moderate specific surface area, relatively balanced overall performance, and good activity and selectivity.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] 1. The present invention adopts the complexation-sol-gel method to prepare the iron-molybdenum catalyst. By adjusting the type and amount of the complexing agent, controlling the pH and drying conditions, catalysts with different morphologies and particle sizes (blocks, large-sized particles, small-sized particles and clusters) can be prepared in a controllable manner, while reducing the generation of free flake MoO3.

[0029] 2. The catalysts of different morphologies and sizes prepared by the present invention have excellent comprehensive performance and different performances: small-sized granular catalysts have high methanol conversion rate, and the methanol content in the produced formaldehyde products is low, which is suitable for industries with high requirements for methanol content; block catalysts have high formaldehyde selectivity and low methanol unit consumption, which is suitable for industries with high production costs; cluster catalysts have high formaldehyde selectivity and are suitable for processes using methanol and water as solvents and formaldehyde as raw materials; large-sized granular catalysts have excellent comprehensive performance and can meet the requirements of most industries.

[0030] 3. The sol-gel method is used to prepare the iron molybdate formaldehyde catalyst, which does not produce any wastewater and is a green and environmentally friendly process. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 is the SEM image of the catalyst in Example 1;

[0032] Figure 2 is the SEM image of the catalyst of Example 2;

[0033] Figure 3 is the SEM image of the catalyst of Example 3;

[0034] Figure 4 is the SEM image of the catalyst of Example 4;

[0035] Figure 5 is the SEM image of the catalyst of Example 5;

[0036] Figure 6 is the SEM image of the catalyst of Example 8;

[0037] Figure 7 is the SEM image of the catalyst of Example 11;

[0038] Figure 8 is a SEM image of the catalyst of Example 14;

[0039] Figure 9 is the SEM image of the catalyst of Comparative Example 1;

[0040] Figure 10 is the SEM image of the catalyst of Comparative Example 2;

[0041] Figure 11 is the SEM image of the catalyst of Comparative Example 3;

[0042] Figure 12 This is the SEM image of the catalyst of Comparative Example 4;

[0043] Figure 13 This is the SEM image of the catalyst of Comparative Example 5;

[0044] Figure 14This is the SEM image of the catalyst of Comparative Example 8;

[0045] Figure 15 is the SEM image of the catalyst of Comparative Example 11;

[0046] Figure 16 This is the SEM image of the catalyst of Comparative Example 14;

[0047] Figure 17 is the SEM image of the catalyst of Comparative Example 17;

[0048] Figure 18 This is the SEM image of the catalyst of Comparative Example 18. DETAILED DESCRIPTION

[0049] The present invention provides a method for preparing a morphology-controllable iron-molybdenum formaldehyde catalyst, comprising the following steps:

[0050] (1) adding ammonium heptamolybdate tetrahydrate to deionized water, and then adding a complexing agent (the molar ratio of the complexing agent to molybdate is 3:1-1:1) thereto to fully dissolve the water to obtain a molybdenum-containing solution having a concentration of ammonium heptamolybdate of 0.04-0.1 mol / L;

[0051] (2) adding ferric nitrate nonahydrate to deionized water, and then adding a complexing agent (the molar ratio of the complexing agent to the iron ion is 3:1-1:1) to fully dissolve the ferric nitrate to obtain an iron-containing solution with a concentration of 0.3-0.5 mol / L of ferric nitrate;

[0052] (3) mixing the molybdenum-containing solution and the iron-containing solution to obtain a mixed solution (the molar atomic ratio of Mo to Fe is 2.2), then adding ammonia water to adjust the pH to 4.0-7.0, and stirring at room temperature for 1-2 hours;

[0053] (4) The solution of step (3) was subjected to vacuum rotary evaporation at 50-75° C. until a sol was formed;

[0054] (5) drying the sol in step (4) in an oven at 90-100° C. for 5-6 h to form a xerogel;

[0055] (6) The dry gel obtained in step (5) is placed in a muffle furnace at 500-550° C. and calcined for 10-12 hours to obtain a finished catalyst.

[0056] The complexing agent in steps (1) and (2) is any one or more of citric acid, oxalic acid, ethylene glycol, ethylenediamine, ethylenediaminetetraacetic acid, glucose and 8-hydroxyquinoline.

[0057] The method of the present invention uses a complexing agent to control the coordination environment of Mo and Fe in the precursor solution, the solution pH, and the evaporation temperature. It is possible to prepare catalysts in small, large, block, and cluster forms, all without the generation of free MoO3 flakes. The prepared catalysts each have advantages in catalytic activity and formaldehyde selectivity. Among them, the block-structured catalyst has lower activity but better formaldehyde selectivity; the small-sized particle-structured catalyst has higher activity; the large-sized particle-structured catalyst has excellent overall performance; and the cluster-structured catalyst has very low activity but excellent formaldehyde selectivity.

[0058] In a specific embodiment of the present invention,

[0059] The preparation method of the block structure catalyst comprises the following steps:

[0060] (1) adding ammonium heptamolybdate tetrahydrate to deionized water, and then adding citric acid as a complexing agent (the molar ratio of the complexing agent to molybdate is 3:1-1:1) to fully dissolve the water to obtain a molybdenum-containing solution having a concentration of ammonium heptamolybdate of 0.04-0.1 mol / L;

[0061] (2) adding ferric nitrate nonahydrate to deionized water, and then adding citric acid as a complexing agent (the molar ratio of the complexing agent to the iron ion is 3:1-1:1) to fully dissolve the ferric nitrate to obtain an iron-containing solution with a concentration of 0.3-0.5 mol / L of ferric nitrate;

[0062] (3) mixing the molybdenum-containing solution and the iron-containing solution to obtain a mixed solution (the molar atomic ratio of Mo to Fe is 2.2), then adding ammonia water to adjust the pH to 4.0-7.0, and stirring at room temperature for 1-2 hours;

[0063] (4) The solution of step (3) was subjected to vacuum rotary evaporation at 50-75° C. until a sol was formed;

[0064] (5) drying the sol in step (4) in an oven at 90-100° C. for 5-6 h to form a xerogel;

[0065] (6) The dry gel obtained in step (5) is placed in a muffle furnace at 500-550° C. and calcined for 10-12 hours to obtain a finished catalyst.

[0066] The preparation method of the small-sized granular catalyst comprises the following steps:

[0067] (1) adding ammonium heptamolybdate tetrahydrate to deionized water, and then adding oxalic acid as a complexing agent (the molar ratio of the complexing agent to molybdate is 3:1-1:1) to fully dissolve the water to obtain a molybdenum-containing solution having a concentration of ammonium heptamolybdate of 0.04-0.1 mol / L;

[0068] (2) adding ferric nitrate nonahydrate to deionized water, and then adding citric acid as a complexing agent (the molar ratio of the complexing agent to the iron ion is 3:1-1:1) to fully dissolve the ferric nitrate to obtain an iron-containing solution with a concentration of 0.3-0.5 mol / L of ferric nitrate;

[0069] (3) mixing the molybdenum-containing solution and the iron-containing solution to obtain a mixed solution (the molar atomic ratio of Mo to Fe is 2.2), then adding ammonia water to adjust the pH to 5.0-6.0, and stirring at room temperature for 1-2 hours;

[0070] (4) The solution of step (3) was evaporated by vacuum rotary evaporation at 75° C. until a sol was formed;

[0071] (5) drying the sol in step (4) in an oven at 90-100° C. for 5-6 h to form a xerogel;

[0072] (6) The dry gel obtained in step (5) is placed in a muffle furnace at 500-550° C. and calcined for 10-12 hours to obtain a finished catalyst.

[0073] The preparation method of the large-size granular catalyst comprises the following steps:

[0074] (1) adding ammonium heptamolybdate tetrahydrate to deionized water, and then adding citric acid (a chelating agent to molybdate molybdate molar ratio of 1:1) to fully dissolve the water to obtain a molybdenum-containing solution having a concentration of 0.04-0.1 mol / L of ammonium heptamolybdate;

[0075] (2) adding ferric nitrate nonahydrate to deionized water, and then adding ethylene glycol as a complexing agent (the molar ratio of the complexing agent to the iron ion is 1:1) to fully dissolve the ferric nitrate to obtain an iron-containing solution with a concentration of 0.3-0.5 mol / L of ferric nitrate;

[0076] (3) mixing the molybdenum-containing solution and the iron-containing solution to obtain a mixed solution (the molar atomic ratio of Mo to Fe is 2.2), then adding ammonia water to adjust the pH to 5.0-7.0, and stirring at room temperature for 1-2 hours;

[0077] (4) The solution of step (3) was subjected to vacuum rotary evaporation at 50-75° C. until a sol was formed;

[0078] (5) drying the sol in step (4) in an oven at 90-100° C. for 5-6 h to form a xerogel;

[0079] (6) The dry gel obtained in step (5) is placed in a muffle furnace at 500-550° C. and calcined for 10-12 hours to obtain a finished catalyst.

[0080] The preparation method of the cluster catalyst comprises the following steps:

[0081] (1) adding ammonium heptamolybdate tetrahydrate to deionized water, and then adding ethylene glycol as a complexing agent (the molar ratio of the complexing agent to molybdate is 2:1-1:1) to fully dissolve the water to obtain a molybdenum-containing solution having a concentration of ammonium heptamolybdate of 0.04-0.1 mol / L;

[0082] (2) adding ferric nitrate nonahydrate to deionized water, and then adding ethylene glycol as a complexing agent (the molar ratio of the complexing agent to the iron ion is 2:1-1:1) to fully dissolve the ferric nitrate to obtain an iron-containing solution with a concentration of 0.3-0.5 mol / L of ferric nitrate;

[0083] (3) mixing the molybdenum-containing solution and the iron-containing solution to obtain a mixed solution (the molar atomic ratio of Mo to Fe is 2.2), then adding ammonia water to adjust the pH to 4.0, and stirring at room temperature for 1-2 hours;

[0084] (4) The solution of step (3) was subjected to vacuum rotary evaporation at 50-70° C. until a sol was formed;

[0085] (5) drying the sol in step (4) in an oven at 90-100° C. for 5-6 h to form a xerogel;

[0086] (6) The dry gel obtained in step (5) is placed in a muffle furnace at 500-550° C. and calcined for 10-12 hours to obtain a finished catalyst.

[0087] The present invention will be further described below with reference to the embodiments.

[0088] Example 1

[0089] A method for preparing a bulk iron-molybdenum formaldehyde catalyst comprises the following steps:

[0090] (1) 9.8 g of ammonium heptamolybdate tetrahydrate (0.0079 mol) was added to 200.0 ml of deionized water, and then 32.0 g of citric acid (0.167 mol, the molar ratio of the complexing agent to the molybdate radical was 3:1) was added thereto and fully dissolved to obtain a molybdenum-containing solution having a concentration of ammonium heptamolybdate of 0.04 mol / L;

[0091] (2) 10.2 g of ferric nitrate nonahydrate (0.025 mol) was added to 50.8 ml of deionized water, and then 14.5 g of citric acid (0.075 mol, the molar ratio of the complexing agent to the iron ion was 3:1) was added thereto and fully dissolved to obtain an iron-containing solution with a ferric nitrate concentration of 0.5 mol / L;

[0092] (3) mixing the molybdenum-containing solution and the iron-containing solution, then adding ammonia water to adjust the pH to 5.0, and stirring at room temperature for 2 h;

[0093] (4) The solution of step (3) was subjected to vacuum rotary evaporation at 50° C. until a sol was formed;

[0094] (5) drying the sol in step (4) in an oven at 100° C. for 6 h to form a xerogel;

[0095] (6) The dry gel obtained in step (5) was placed in a muffle furnace at 500°C and calcined for 12 hours to obtain a bulk iron-molybdenum formaldehyde catalyst. The SEM image of the catalyst is shown in FIG. Figure 1 .

[0096] Example 2

[0097] A method for preparing a small-particle iron-molybdenum formaldehyde catalyst comprises the following steps:

[0098] (1) 9.8 g of ammonium heptamolybdate tetrahydrate was added to 82.5 ml of deionized water, and then 10.0 g of oxalic acid (0.11 mol, the molar ratio of the complexing agent to the molybdate radical is 2:1) was added thereto and fully dissolved to obtain a molybdenum-containing solution having a concentration of 0.1 mol / L of ammonium heptamolybdate;

[0099] (2) 10.2 g of ferric nitrate nonahydrate was added to 83.7 ml of deionized water, and then 9.7 g of citric acid (0.05 mol, the molar ratio of the complexing agent to the iron ion was 2:1) was added thereto and fully dissolved to obtain an iron-containing solution with a ferric nitrate concentration of 0.3 mol / L;

[0100] (3) mixing the molybdenum-containing solution and the iron-containing solution, then adding ammonia water to adjust the pH to 6.0, and stirring at room temperature for 2 h;

[0101] (4) The solution of step (3) was evaporated by vacuum rotary evaporation at 75° C. until a sol was formed;

[0102] (5) drying the sol in step (4) in an oven at 100° C. for 6 h to form a xerogel;

[0103] (6) The dry gel obtained in step (5) was placed in a muffle furnace at 500°C and calcined for 12 hours to obtain a small particle iron-molybdenum formaldehyde catalyst (particle size of 20-100 nm). The SEM image of the catalyst is shown in FIG. Figure 2 .

[0104] Example 3

[0105] A method for preparing a large-particle iron-molybdenum formaldehyde catalyst comprises the following steps:

[0106] (1) 9.8 g of ammonium heptamolybdate tetrahydrate was added to 113.2 ml of deionized water, and then 10.7 g of citric acid (0.055 mol, the molar ratio of the complexing agent to the molybdate radical was 1:1) was added thereto and fully dissolved to obtain a molybdenum-containing solution having a concentration of 0.07 mol / L of ammonium heptamolybdate;

[0107] (2) 10.2 g of ferric nitrate nonahydrate was added to 63.3 ml of deionized water, and then 1.6 g of ethylene glycol (0.025 mol, the molar ratio of the complexing agent to the iron ion was 1:1) was added thereto and fully dissolved to obtain an iron-containing solution with a ferric nitrate concentration of 0.4 mol / L;

[0108] (3) mixing the molybdenum-containing solution and the iron-containing solution, then adding ammonia water to adjust the pH to 6.0, and stirring at room temperature for 2 h;

[0109] (4) The solution of step (3) was evaporated by vacuum rotary evaporation at 75° C. until a sol was formed;

[0110] (5) drying the sol in step (4) in an oven at 100° C. for 6 h to form a xerogel;

[0111] (6) The dry gel obtained in step (5) was placed in a muffle furnace at 500°C and calcined for 12 hours to obtain a large particle iron-molybdenum formaldehyde catalyst (particle size of 100-300nm). The SEM image of the catalyst is as follows Figure 3 .

[0112] Example 4

[0113] A method for preparing a clustered iron-molybdenum formaldehyde catalyst comprises the following steps:

[0114] (1) 9.8 g of ammonium heptamolybdate tetrahydrate was added to 113.2 ml of deionized water, and then 3.4 g of ethylene glycol (0.055 mol, the molar ratio of the complexing agent to the molybdate radical was 1:1) was added thereto and fully dissolved to obtain a molybdenum-containing solution having a concentration of 0.07 mol / L of ammonium heptamolybdate;

[0115] (2) 10.2 g of ferric nitrate nonahydrate was added to 63.3 ml of deionized water, and then 1.6 g of ethylene glycol (the molar ratio of the complexing agent to the iron ion was 1:1) was added thereto and fully dissolved to obtain an iron-containing solution with a concentration of 0.4 mol / L of ferric nitrate;

[0116] (3) mixing the molybdenum-containing solution and the iron-containing solution, then adding ammonia water to adjust the pH to 4.0, and stirring at room temperature for 2 h;

[0117] (4) The solution of step (3) was subjected to vacuum rotary evaporation at 50° C. until a sol was formed;

[0118] (5) drying the sol in step (4) in an oven at 100° C. for 6 h to form a xerogel;

[0119] (6) The dry gel obtained in step (5) was placed in a muffle furnace at 500°C and calcined for 12 hours to obtain a clustered iron-molybdenum formaldehyde catalyst. The SEM image of the catalyst is shown in FIG. Figure 4 .

[0120] The catalyst was prepared by changing the raw materials, ratios, reaction parameters, etc. in Example 1. The specific parameters are shown in Table 1:

[0121] Table 1

[0122]

[0123]

[0124] We adopted the research method of controlling variables and changed the preparation conditions of the above examples 1-16 to conduct comparative studies. The SEM image of the catalyst in Example 5 is shown in FIG. Figure 5 ; The SEM picture of Example 8 catalyst is as follows Figure 6 ; The SEM image of the catalyst of Example 11 is as follows Figure 7 ; The SEM image of Example 14 catalyst is as follows Figure 8 .

[0125] Comparative Example 1

[0126] A method for preparing an iron-molybdenum formaldehyde catalyst comprises the following steps:

[0127] (1) 9.8 g of ammonium heptamolybdate tetrahydrate was added to 200.0 ml of deionized water, and then 32.0 g of citric acid (the molar ratio of the complexing agent to the molybdate radical was 3:1) was added thereto and fully dissolved to obtain a molybdenum-containing solution having a concentration of 0.04 mol / L of ammonium heptamolybdate;

[0128] (2) 10.2 g of ferric nitrate nonahydrate was added to 50.8 ml of deionized water and fully dissolved without adding a complexing agent to obtain an iron-containing solution with a concentration of 0.5 mol / L of ferric nitrate;

[0129] (3) mixing the molybdenum-containing solution and the iron-containing solution, then adding ammonia water to adjust the pH to 5.0, and stirring at room temperature for 2 h;

[0130] (4) The solution of step (3) was subjected to vacuum rotary evaporation at 50° C. until a sol was formed;

[0131] (5) drying the sol in step (4) in an oven at 100° C. for 6 h to form a xerogel;

[0132] (6) The dry gel obtained in step (5) was placed in a muffle furnace at 500°C and calcined for 12 hours to obtain a catalyst with the morphology of agglomerated particles + flakes. The SEM image of the catalyst is as follows: Figure 9 .

[0133] Comparative Example 2

[0134] A method for preparing an iron-molybdenum formaldehyde catalyst comprises the following steps:

[0135] (1) 9.8 g of ammonium heptamolybdate tetrahydrate was added to 82.5 ml of deionized water, and then 10.0 g of oxalic acid (the molar ratio of the complexing agent to the molybdate radical was 2:1) was added thereto and fully dissolved to obtain a molybdenum-containing solution having a concentration of 0.1 mol / L of ammonium heptamolybdate;

[0136] (2) 10.2 g of ferric nitrate nonahydrate was added to 83.7 ml of deionized water, and then 9.7 g of citric acid (the molar ratio of the complexing agent to the iron ion was 2:1) was added thereto and fully dissolved to obtain an iron-containing solution with a concentration of 0.3 mol / L of ferric nitrate;

[0137] (3) mixing the molybdenum-containing solution and the iron-containing solution, then adding ammonia water to adjust the pH to 6.0, and stirring at room temperature for 2 h;

[0138] (4) The solution of step (3) was evaporated by vacuum rotary evaporation at 40° C. until a sol was formed;

[0139] (5) drying the sol in step (4) in an oven at 100° C. for 6 h to form a xerogel;

[0140] (6) The dry gel obtained in step (5) was placed in a muffle furnace at 500°C and calcined for 12 hours to obtain a catalyst with a granular + flake morphology. The SEM image of the catalyst is as follows: Figure 10 .

[0141] Comparative Example 3

[0142] A method for preparing an iron-molybdenum formaldehyde catalyst comprises the following steps:

[0143] (1) 9.8 g of ammonium heptamolybdate tetrahydrate was added to 113.2 ml of deionized water, and then 10.0 g of oxalic acid (the molar ratio of the complexing agent to the molybdate radical was 2:1) was added thereto and fully dissolved to obtain a molybdenum-containing solution having a concentration of 0.07 mol / L of ammonium heptamolybdate;

[0144] (2) 10.2 g of ferric nitrate nonahydrate was added to 63.3 ml of deionized water, and then 1.6 g of ethylene glycol (the molar ratio of the complexing agent to the iron ion was 2:1) was added thereto and fully dissolved to obtain an iron-containing solution with a concentration of 0.4 mol / L of ferric nitrate;

[0145] (3) mixing the molybdenum-containing solution and the iron-containing solution, then adding ammonia water to adjust the pH to 6.0, and stirring at room temperature for 2 h;

[0146] (4) The solution of step (3) was evaporated by vacuum rotary evaporation at 75° C. until a sol was formed;

[0147] (5) drying the sol in step (4) in an oven at 100° C. for 6 h to form a xerogel;

[0148] (6) The dry gel obtained in step (5) was placed in a muffle furnace at 500°C and calcined for 12 hours to obtain a catalyst with a granular + flake morphology. The SEM image of the catalyst is as follows: Figure 11 .

[0149] Comparative Example 4

[0150] A method for preparing an iron-molybdenum formaldehyde catalyst comprises the following steps:

[0151] (1) 9.8 g of ammonium heptamolybdate tetrahydrate was added to 113.2 ml of deionized water, and then 3.4 g of ethylene glycol (the molar ratio of the complexing agent to the molybdate radical was 1:1) was added thereto to fully dissolve the mixture to obtain a molybdenum-containing solution having a concentration of 0.07 mol / L of ammonium heptamolybdate;

[0152] (2) 10.2 g of ferric nitrate nonahydrate was added to 63.3 ml of deionized water, and then 1.6 g of ethylene glycol (the molar ratio of the complexing agent to the iron ion was 1:1) was added thereto and fully dissolved to obtain an iron-containing solution with a concentration of 0.4 mol / L of ferric nitrate;

[0153] (3) mixing the molybdenum-containing solution and the iron-containing solution, then adding ammonia water to adjust the pH to 7.0, and stirring at room temperature for 2 h;

[0154] (4) The solution of step (3) was subjected to vacuum rotary evaporation at 50° C. until a sol was formed;

[0155] (5) drying the sol in step (4) in an oven at 100° C. for 6 h to form a xerogel;

[0156] (6) The dry gel obtained in step (5) was placed in a muffle furnace at 500°C and calcined for 12 hours to obtain a catalyst with a granular + flake morphology. The SEM image of the catalyst is as follows: Figure 12 .

[0157] Comparative Examples 5-16

[0158] The catalyst was prepared by changing the raw materials, ratios, reaction parameters, etc. in Example 1. The specific parameters are shown in Table 2:

[0159] Table 2

[0160]

[0161] The SEM image of the catalyst of Comparative Example 5 is as follows: Figure 13 ; The SEM picture of the catalyst of Comparative Example 8 is as follows Figure 14 ; The SEM image of the catalyst of Comparative Example 11 is as follows Figure 15 ; The SEM image of the catalyst of Comparative Example 14 is as follows Figure 16 .

[0162] Comparative Example 17

[0163] A method for preparing an iron-molybdenum formaldehyde catalyst by a coprecipitation method, comprising the following steps:

[0164] (1) 9.8 g of ammonium heptamolybdate tetrahydrate was added to 113.2 ml of deionized water and fully dissolved without adding a complexing agent to obtain a molybdenum-containing solution with a concentration of 0.07 mol / L of ammonium heptamolybdate;

[0165] (2) 10.2 g of ferric nitrate nonahydrate was added to 63.3 ml of deionized water and fully dissolved without adding a complexing agent to obtain an iron-containing solution with a concentration of 0.5 mol / L of ferric nitrate;

[0166] (3) mixing the molybdenum-containing solution and the iron-containing solution, then adding ammonia water to adjust the pH to 2.0, and stirring at room temperature for 2 h;

[0167] (4) stirring the solution in step (3) at 80° C. for 4 h and filtering while hot to obtain a filter cake;

[0168] (5) drying the filter cake from step (4) in an oven at 100° C. for 12 h;

[0169] (6) The dry gel obtained in step (5) was placed in a muffle furnace at 500°C and calcined for 12 hours to obtain a catalyst with a granular + flake morphology. The SEM image of the catalyst is as follows: Figure 17 .

[0170] Comparative Example 18

[0171] The commercial catalyst FH44 purchased from Johnson Matthey was used as comparative example 18. The SEM image of the catalyst is shown in FIG. Figure 18 .

[0172] The catalysts prepared in Examples 1-16 and Comparative Examples 1-17 and the commercial catalyst of Comparative Example 18 were evaluated in a fixed-bed microreactor catalytic reaction device to determine the catalyst performance, including catalyst activity (methanol conversion rate) and selectivity (formaldehyde, dimethyl ether, CO and CO2).

[0173] Catalyst Evaluation Method: A fixed-bed reactor with an inner diameter of 8.0 mm was loaded with 0.5 g of catalyst. A thermocouple was inserted into the catalyst bed. Anhydrous methanol (at a flow rate of 0.02 ml / min) was pumped into the reaction tube via a micro-plunger pump. The feed gas was then passed through a mass flow controller at a total flow rate of 240 ml / min (N₂:O₂ volume ratio of 7:1). The reaction temperature was measured by a thermocouple inserted into the bed. The product at the reaction outlet was held at 120°C, sampled using a ten-way valve, and injected. The component contents were analyzed online by gas chromatography. The results are shown in Table 3.

[0174] Table 3

[0175]

[0176]

[0177] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A method for preparing a morphology-controllable iron-molybdenum formaldehyde catalyst, characterized in that: The following steps are involved: (1) adding ammonium heptamolybdate tetrahydrate to deionized water, then adding a complexing agent therein and fully dissolving it to obtain a molybdenum-containing solution; (2) adding ferric nitrate nonahydrate to deionized water, and then adding a complexing agent thereto to fully dissolve the ferric nitrate to obtain an iron-containing solution; (3) mixing the molybdenum-containing solution and the iron-containing solution to obtain a mixed solution, then adding ammonia to adjust the pH to 4.0-7.0, and stirring at room temperature; (4) vacuum rotary evaporation of the solution in step (3) to form a sol; (5) drying the sol from step (4) to form a xerogel; (6) The xerogel obtained in step (5) is placed in a muffle furnace and calcined to obtain a finished catalyst product.

2. The method for preparing a morphology-controllable iron-molybdenum formaldehyde catalyst according to claim 1, wherein: The concentration of ammonium heptamolybdate in the molybdenum-containing solution in step (1) is 0.04-0.1 mol / L; the molar ratio of the complexing agent to molybdate is 3:1-1:

1.

3. The method for preparing a morphology-controllable iron-molybdenum formaldehyde catalyst according to claim 1, wherein: The concentration of ferric nitrate in the iron-containing solution in step (2) is 0.3-0.5 mol / L; the molar ratio of the complexing agent to the iron ion is 3:1-1:

1.

4. The method for preparing a morphology-controllable iron-molybdenum formaldehyde catalyst according to claim 1, wherein: The complexing agent in step (1) and step (2) is any one or more of citric acid, oxalic acid, ethylene glycol, ethylenediamine, ethylenediaminetetraacetic acid, glucose and 8-hydroxyquinoline.

5. The method for preparing a morphology-controllable iron-molybdenum formaldehyde catalyst according to claim 1, wherein: The molar atomic ratio of Mo to Fe in the mixed solution of step (3) is 2.1-2.

3.

6. The method for preparing a morphology-controllable iron-molybdenum formaldehyde catalyst according to claim 1, wherein: The stirring time at room temperature in step (3) is 1-2h.

7. The method for preparing a morphology-controllable iron-molybdenum formaldehyde catalyst according to claim 1, wherein: The temperature of the vacuum rotary evaporation in step (4) is 50-75°C.

8. The method for preparing a morphology-controllable iron-molybdenum formaldehyde catalyst according to claim 1, wherein: The drying temperature in step (5) is 90-100° C. and the drying time is 5-6 hours.

9. The method for preparing a morphology-controllable iron-molybdenum formaldehyde catalyst according to claim 1, wherein: The calcination temperature in step (6) is 500-550°C.

10. The method for preparing a morphology-controllable iron-molybdenum formaldehyde catalyst according to claim 1, wherein: The calcination time in step (6) is 10 to 12 hours.

Citation Information

Patent Citations

  • Preparation method of iron molybdenum based catalyst for preparing formaldehyde by methanol oxidation and application

    CN108097259A

  • Coating type catalyst for preparing formaldehyde through methanol oxidation by iron-molybdenum method and preparation method thereof.

    CN112657504A

  • Catalyst for formaldehyde production and preparation method thereof

    CN118925738A

  • Process for manufacturing GELS containing molybdenum and iron and their uses

    GB1282949A

Cited By

  • Iron-molybdenum catalyst for oxidation of methanol to formaldehyde and preparation method thereof

    CN122377482A

  • Atmosphere gradient calcination method for iron-molybdenum catalyst

    CN122605586A